(untitled) (Journal of Electrical Engineering, 2011)
Transportation is a large and important part of the economy of a country, train is one of the main transportation systems of Bangladesh. Therefore, we should have a good and strong monitoring system that can locate a train at every instant. This paper has proposed the implementation of a global positioning system (GPS) based train monitoring system that could locate a train at every instant. Here a GPSGPRS module transmits the location information to a web server. Every track in the system will be assigned a unique number. Now this track position of the train is also transmitted with this location information via an onboard computer placed on the train. This computer continuously updates the track position when the train is moving. This information is stored in the web server. When a client user requests for a particular train status, a web application shows the status in Google map. This implementation can effectively reduce train accidents in Bangladesh. Index Terms: global positioning system (GPS); tracking; monitoring system; web server; Google map. J. Elec. Engg., Instn. Engrs., Bangladesh, 36(II), December 2009: 35-38